Pathophysiology of fatal falciparum malaria in African children. - Newton, C; Taylor, T; Whitten, R (1998)
Children living in sub-Saharan Africa bear the brunt of the mortality from falciparum malaria, yet there is a dearth of relevant post-mortem data. Clinical studies from centers in Africa suggest that the pathophysiology of severe malaria is different in children and adults. Three overlapping clinical syndromes, metabolic acidosis manifesting as hyperpnea, cerebral malaria, and severe anemia, are responsible for nearly all the deaths in African children. Despite improvements in antimalarial treatment, there has not been a significant reduction in mortality. We review the pathology and pathophysiology of fatal falciparum malaria in African children. Many questions remain, the answers to which would facilitate the development and evaluation of new approaches to the management of this disease.